Factors contributing to nitrate contamination in a groundwater recharge area of the North China Plain. Issue 13 (6th March 2016) - Wang, Shiqin; Tang, Changyuan; Song, Xianfang; Yuan, Ruiqiang; Han, Zhiwei; Pan, Yun
Abstract: Nitrate contamination is a common problem in groundwater of the North China Plain (NCP) owing to overuse of fertilizers and discharge of wastewater. Accordingly, it is important to investigate nitrate contamination in recharge areas to understand the fate of nitrate in the plains area. In this study, the spatial and temporal distribution characteristics of nitrate and factors contributing to its sources and transformation in shallow groundwater of the Beiyishui River watershed, NCP, were analysed by a combination of multiple regression and multi‐tracer methods. The nitrate concentration of 79% of the samples exceeded the natural environmental standard of 13.3 mg l −1, while that of 23% of the samples exceeded the World Health Organization (WHO) drinking water standard of 50 mg l −1 . Groundwater age estimation of the hill regions based on chlorofluorocarbons (CFCs) revealed a mix of young water from 1982 to 1990 and old, low CFC water. The analysis based on the variations in land use in past years revealed that part of the grassland was converted into woodland between 1980 and 1995; therefore, the land use at the recharge time was used to determine which surface conditions influence groundwater nitrate concentrations. Multiple regression analysis showed that point source pollution contributed to the high concentration of nitrate in the hill region. Fertilizer application associated with land use change from grassland to woodland was also related to the present nitrate concentration. In the plains area, the contribution of fresh water from fault fractures and denitrification led to 31 to 72% and 6 to 51% reductions in nitrate concentrations, respectively. Our results suggested that controlling point source contamination and fertilizer input to hilly regions of the study will prevent groundwater of the plains area from deterioration in future years by mixing fresh water into the aquifers and decreasing denitrification, and therefore nitrate concentrations. Copyright © 2015 John Wiley & Sons, Ltd.